2006
DOI: 10.1017/s0031182006001168
|View full text |Cite
|
Sign up to set email alerts
|

High polymorphism in Plasmodium vivax merozoite surface protein-5 (MSP5)

Abstract: A key issue relating to developing multi-component anti-malarial vaccines, lies in studying Plasmodium vivax surface proteins' genetic variation. The present work was aimed at amplifying, cloning and sequencing the gene encoding P. vivax merozoite surface protein 5 (PvMSP5) in samples obtained from infected patients from Colombian areas having varying malaria transmission rates. Nucleotide sequence data reported in this paper are available in the GenBank, EMBL and DDBJ databases under Accessions numbers DQ3415… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
26
3

Year Published

2009
2009
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 61 publications
(60 reference statements)
6
26
3
Order By: Relevance
“…As expected, results demonstrated that MSP proteins are immunogenic in natural infections. Moreover, results confirmed that MSP1-19 is more immunogenic than MSP1-N [20] and that in spite of MSP5 being highly polymorphic [34], it is also highly immunogenic. Furthermore, in line with being a multigene family differentially expressed during blood stages [35], reactivity against MSP7 was lower than MSP1 or MSP5.…”
Section: Discussionmentioning
confidence: 73%
“…As expected, results demonstrated that MSP proteins are immunogenic in natural infections. Moreover, results confirmed that MSP1-19 is more immunogenic than MSP1-N [20] and that in spite of MSP5 being highly polymorphic [34], it is also highly immunogenic. Furthermore, in line with being a multigene family differentially expressed during blood stages [35], reactivity against MSP7 was lower than MSP1 or MSP5.…”
Section: Discussionmentioning
confidence: 73%
“…The highly polymorphic Pv MSP-5 contains potential signal and glycosylphosphatidyl inositol (GPI) anchor sequences and a single EGF-like domain near the carboxyl-terminus [55]. Pv MSP-5 has been localized to the apical end of merozoites [56].…”
Section: Resultsmentioning
confidence: 99%
“…19) of the Ministry of Health in Papua New Guinea, and consent was obtained from parents or legal guardians before recruitment of each patient. Blood samples, obtained via finger prick, were collected into EDTA microtainer tubes, and DNA was extracted using a QIAamp DNA blood kit (Qiagen) according to the manufacturer's instructions.…”
Section: Subjects Materials and Methodsmentioning
confidence: 99%
“…Sequencing revealed msp1 as highly polymorphic, with 31 alleles among 40 isolates analyzed [17]. High diversity was also detected in msp3␤ [18], msp5 [18,19], and dpb [20 -22].…”
mentioning
confidence: 99%